Emotional Physiology and Consolatory Etiquette Reading the Present Indicative with Future Reference in the Eschatological Statement in 1 Peter 1:6 - Martin, Troy W. 1953- (2016)
Although present tense in form, the verb ἀγαλλιᾶσθε in 1 Pet 1:6 is read contextually with future reference by commentators and translators who distinguish between present grieving and future rejoicing. This interpretation of 1 Pet 1:6 dominated until the Reformation, when John Calvin and Conrad Horneius argued that the present tense form of ἀγαλλιᾶσθε takes precedence over the context. Their reading assumes that the recipients of this letter simultaneously experience rejoicing and grieving, and Calvin and Horneius appealed to the experience of their sixteenth-century readers for proof that humans can have such conflicting emotions. In this article, I evaluate this assumption by examining ancient discussions of the emotions that treat joy and grief as opposites, with the former as pleasurable and the latter as painful. I demonstrate that these emotions cannot be experienced simultaneously according to ancient physiology. I also evaluate the tendency to read ἀγαλλιᾶσθε with present reference by examining ancient consolatory etiquette and conclude that informing these grieving recipients at the beginning of the letter that they are rejoicing would be inappropriate and contrary to consolatory etiquette, theory, and practice. Even though almost all recent Petrine commentators follow Calvin and Horneius in reading ἀγαλλιᾶσθε in reference to present rejoicing, I demonstrate that ancient physiology and consolatory etiquette support the pre-Reformation reading of this verb in reference to future rejoicing.
Keywords: Bible. Peter, 1st; Calvin, Jean, 1509-1564; Christianity; EMOTIONS (Psychology); Grief; Joy; Reformation; Religious Aspects